SEMIOTIKA DALAM TARI : STUDI KASUS TARI DOLALAK - Indriyanto, R.; Laura, Pauline Lidya; Astuti, Budi (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2023)
Dolalak Dance is a dance themed around the joy of Dutch soldiers. Dolalak Dance serves as a sign that displays specific meanings perceived by the community as a sign that interprets symbolic meanings. The Dolalak Budi Santoso group also offers symbolic meanings in their performance. The purpose of this research is to understand the semiotics of the Dolalak Dance performance in Kaliharjo Village, Purworejo Regency. This research utilizes a descriptive qualitative approach, semiotic approach, and etic-emic approach. The main focus of this research is to explore the symbolic meanings of a performance through a semiotic approach. With a semiotic approach, the Dolalak performance is placed as a sign and understood as a signifier by the community. Data validity is ensured through triangulation technique. Data analysis involves description and interpretation techniques. The results of this research show that the semiotics of Dolalak Dance can be seen through symbolic meanings in the form of presentational symbols and discursive symbols within the elements of the performance. Dolalak Dance presents presentational symbols through visual and auditory elements depicting the joy and agility of Dutch soldiers. The discursive symbols of Dolalak Dance are revealed through non-iconic elements of the performance, representing values of goodness and life. In conclusion, the semiotics of Dolalak Dance manifest in the symbolic meanings that arise from the perception of individuals or the community towards the form of the Dolalak Dance performance